2016
DOI: 10.1177/1947603516659344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Validation of Chondrogenic Differentiation and Hypoxia Responsiveness of Platelet-Lysate Expanded Adipose Tissue–Derived Human Mesenchymal Stromal Cells

Abstract: Objective: To determine the optimal environmental conditions for chondrogenic differentiation of human adipose tissue-derived mesenchymal stromal/stem cells (AMSCs). In this investigation we specifically investigate the role of oxygen tension and 3-dimensional (3D) culture systems. Design: Both AMSCs and primary human chondrocytes were cultured for 21 days in chondrogenic media under normoxic (21% oxygen) or hypoxic (2% oxygen) conditions using 2 distinct 3D culture methods (high-density pellets and poly-ε-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…Our data revealed a significantly higher expression of HIF-1α at 7 and 14 days in chondrospheroids cultured under hypoxia than in those cultured under normoxia, which explains the higher COL2A1 and aggrecan expression at the same time points. These findings are in line with those obtained by other authors, in which hypoxic conditions were associated with the increased expression of cartilage-related biomarkers and biosynthesis of a glycosaminoglycan-positive matrix in 3D structures [15,49] and the maintenance of the chondrogenic phenotype in chondrocytes [50].…”
Section: Discussionsupporting
confidence: 92%
“…Our data revealed a significantly higher expression of HIF-1α at 7 and 14 days in chondrospheroids cultured under hypoxia than in those cultured under normoxia, which explains the higher COL2A1 and aggrecan expression at the same time points. These findings are in line with those obtained by other authors, in which hypoxic conditions were associated with the increased expression of cartilage-related biomarkers and biosynthesis of a glycosaminoglycan-positive matrix in 3D structures [15,49] and the maintenance of the chondrogenic phenotype in chondrocytes [50].…”
Section: Discussionsupporting
confidence: 92%
“…Schallmoser et al and Capelli et al also reported the feasibility of clinical scale expansion of MSCs from BM aspirate without any prior manipulation using HPL . It has also been reported that use of HPL enhances osteogenic and chondrogenic differentiation capabilities of MSCs in vitro .…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the stable expression of Col10a1 in our study indicated that hADSCs might approach an end-stage differentiation. The decreasing relative transcription level of COMP from day 7 to day 14 and increasing Col10a1 expression were also observed in human chondrocytes when cultured in a cell culture incubator (Galeano-Garces et al, 2017). Consequently, GAG products from differentiated cells did not aggregate enough to form a large amount of aggrecan.…”
Section: Gapdhmentioning
confidence: 85%